Prognostic Impact of Pancoronary Quantitative Flow Ratio Assessment in Patients Undergoing Percutaneous Coronary Intervention for Acute Coronary Syndromes. (December 2021) - Erbay, Aslihan; Penzel, Lisa; Abdelwahed, Youssef S.; Klotsche, Jens; Heuberger, Andrea; Schatz, Anne-Sophie; Steiner, Julia; Haghikia, Arash; Sinning, David; Fröhlich, Georg M.; Landmesser, Ulf; Stähli, Barbara E.; et al.
Abstract : Background: Quantitative flow ratio (QFR) has been introduced as a novel angiography-based modality for fast hemodynamic assessment of coronary artery lesions and validated against fractional flow reserve. This study sought to define the prognostic role of pancoronary QFR assessment in patients with acute coronary syndrome (ACS) including postinterventional culprit and nonculprit vessels. Methods: In a total of 792 patients with ACS (48.6% ST-segment–elevation ACS and 51.4% non–ST-segment–elevation ACS), QFR analyses of postinterventional culprit (n=792 vessels) and nonculprit vessels (n=1231 vessels) were post hoc performed by investigators blinded to clinical outcomes. The follow-up comprised of major adverse cardiovascular events, including all-cause mortality, nonfatal myocardial infarction, and ischemia-driven coronary revascularization within 2 years after the index ACS event. Results: Major adverse cardiovascular events as composite end point occurred in 99 patients (12.5%). QFR with an optimal cutoff value of 0.89 for postinterventional culprit vessels and 0.85 for nonculprit vessels emerged as independent predictor of major adverse cardiovascular events after ACS (nonculprit arteries: adjusted odds ratio, 3.78 [95% CI, 2.21–6.45], P <0.001 and postpercutaneous coronary intervention culprit arteries: adjusted odds ratio, 3.60 [95% CI, 2.09–6.20], P <0.001). Conclusions: The present study for the first time demonstrates the prognostic implications of a pancoronary angiography-based functional lesion assessment in patients with ACS. Hence, QFR offers a novel tool to advance risk stratification and guide therapeutic management after ACS. Abstract : Supplemental Digital Content is available in the text.